CURVED DIPOLAR ELECTROMAGNET, NUMERICAL MODELING AND DESIGN (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
A conceptual design for a normal conducting curved magnet, which, after optimization, is the current best design that achieves the requirements for the generated magnetic field, is proposed. The primary purpose of the analytical effort, the results of which are presented, is to develop a viable engineering design satisfying requirements to the parameters of the generated magnetic field and the electromagnet functional and structural ones. The work includes the proposed conceptual approaches, modeling analysis of the generated magnetic field, and the technical design for the conductor and winding pack parameters. The magnet's structural design, the winding's heating, the designed parameters of the electromagnet cooling system, and the power supply parameters are also provided.
Keywords: curved electromagnet; dipole; finite element analysis; Electromagnetic field (EMF); design